PENINDASAN RAS KULIT PUTIH EROPA TERHADAP RAS KULIT HITAM AFRIKA DALAM CERPEN â€œA BLACK-SKINNED GIRLâ€ KARYA SEMBENE OUSMANE (Kajian Pendekatan Poskolonial) - Hadiyanto Hadiyanto (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2008)
Colonialism continuously brings about the complexity of excess either to the colonizing country or the colonized country. This essay discusses the post-colonialism effect on African society reflected in Sembene Ousmaneâ€™s A Black Skinned Girl. It tells an African black skinned-girl with her obsession to be a successful housemaid in France, yet living a life in misery and sorrows she has passed through every day as a result of her mistressâ€™s colonial conduct. The European white-skinned woman does such a cruel treatment to the African black skinned-girl since she thinks that she has a very dissenting cultural and racial identity. Anti-colonial resistance done by the African black skinned-girl really means nothing, not changing the heart-breaking fate but her death. Not merely oppression, but also African natural resource richness that her white-skinned master and mistress have already exploited.